1994
DOI: 10.1007/bf00037584
|View full text |Cite
|
Sign up to set email alerts
|

Growth of embryogenic sweet orange callus on media varying in the ratio of nitrate to ammonium nitrogen

Abstract: Embryogenic callus from Citrus sinensis (L.) Osbeck cv. Hamlin was cultured for 28 days on 20 media arranged in a 5 x 2 × 2 factorial varying in the ratio of nitrate to ammonium nitrogen, total inorganic nitrogen, and benzyladenine. Fresh weight increase of callus and final medium pH were significantly affected by total inorganic nitrogen and the ratio of nitrate to ammonium. The nitrate to ammonium ratio accounted for 55% of the variation in the fresh weight increase of the callus and 93% of the variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Sodium is a trace element important for some plants (Salisbury and Ross 1992), but its role on the micropropagation process has not been evaluated. Finally, we can speculate that these variations in the mineral composition can interfere with membrane transport and affect the pH of plant cells, thus influencing the in vitro response (Niedz 1994). However, it should be noted that experiments performed with A. unedo and other Ericaceae indicate that different culture media, other cytokinins, and sucrose were also able to promote shoot proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…Sodium is a trace element important for some plants (Salisbury and Ross 1992), but its role on the micropropagation process has not been evaluated. Finally, we can speculate that these variations in the mineral composition can interfere with membrane transport and affect the pH of plant cells, thus influencing the in vitro response (Niedz 1994). However, it should be noted that experiments performed with A. unedo and other Ericaceae indicate that different culture media, other cytokinins, and sucrose were also able to promote shoot proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…The absorption of NO 3 -anions results in increased pH levels due to an excretion of HCO 3 -from the explant. Conversely, absorption of NH 4 + cations results in a release of H + reducing the pH of the medium (Niedz 1994). Thus, in the present work the latter negative effects of inorganic N sources were avoided by adding arginine, as organic nitrogen, to the culture medium.…”
Section: Effect Of Arginine On Induction Of Somatic Embryogenesismentioning
confidence: 95%
“…Studies with Pinus strobus L. revealed a total inhibition of callus growth if ammonium was the only nitrogen source available [42], and Oryza sativa L. suspension cultures showed inhibited growth if given ammonium [43]. Furthermore, Citrus sinensis (L.) Osbeck embryogenic callus growth was significantly reduced if the majority of inorganic nitrogen was supplied as ammonium [44]. Another study carried out with Oryza sativa cells found that L-glutamine supplementation had no positive effect on the internal ammonium content [45].…”
Section: Morphological and Developmental Characterization And Nitrogmentioning
confidence: 99%